Design and Development of Alternative Energy Sources: Solar Power Plant in Kalandrina Selosia Residential Area RT 008 / RW 008 Jayamukti Village - Alfian Ady Saputra; Efi Anisa (Institut Teknologi dan Bisnis Asia Malang, 2023)
Purpose: This research paper aims to introduce a solar power plant in Kalandrina Selosia's residential area, addressing local energy needs sustainably. The study's significance lies in offering a renewable energy solution within a community context. Method: The research used experimental and descriptive methods to measure solar panel output and intensity alongside assessing electrical installations. Analytical techniques evaluated the system's functionality. Practical Applications: The designed 50-watt solar power plant showcases the feasibility of local solar energy generation. Its potential to reduce costs and environmental impact holds practical implications for communities lacking conventional power sources. Conclusion: This study successfully demonstrates solar power's viability in Kalandrina Selosia. The project contributes practical insight into renewable energy adoption, benefiting the community and broader understanding.